2006
DOI: 10.1369/jhc.6a7063.2006
|View full text |Cite
|
Sign up to set email alerts
|

Embedding of Bone Samples in Methylmethacrylate: A Suitable Method for Tracking LacZ Mesenchymal Stem Cells in Skeletal Tissues

Abstract: S U M M A R Y Considerable research has been focused on the use of bone marrow-derived mesenchymal stem cells (MSCs) for the repair of non-unions and bone defects. To date, the question of whether transplanted MSCs survive and engraft within newly formed tissue remains unresolved. The development of an easy and reliable method that would allow cell fate monitoring in transplant recipients is a pressing concern for the field of tissue engineering. To demonstrate the presence of transplanted cells in newly forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Some authors reported longer survival, up to 5 months in Nude mice, when the cells were associated with matrices such as Matrigel or type I collagen, which are thought to trigger lower inflammatory reaction than calcium phosphate biomaterials. 22,28,[45][46][47] The results obtained by Tasso et al, which show identical survival times (1 week) when C57BL/6 mouse BMSCs were grafted in syngenic or nude recipients, suggest that species specificity of donor cells is also probably involved. 22 In conclusion, using quantitative methods based on the detection of the Y chromosome, we show here in a syngenic model of SC bone formation that BMSCs die within 3 weeks after implantation, whereas host cells colonize massively the biomaterial, leading to the centripetal formation of new bone.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Some authors reported longer survival, up to 5 months in Nude mice, when the cells were associated with matrices such as Matrigel or type I collagen, which are thought to trigger lower inflammatory reaction than calcium phosphate biomaterials. 22,28,[45][46][47] The results obtained by Tasso et al, which show identical survival times (1 week) when C57BL/6 mouse BMSCs were grafted in syngenic or nude recipients, suggest that species specificity of donor cells is also probably involved. 22 In conclusion, using quantitative methods based on the detection of the Y chromosome, we show here in a syngenic model of SC bone formation that BMSCs die within 3 weeks after implantation, whereas host cells colonize massively the biomaterial, leading to the centripetal formation of new bone.…”
mentioning
confidence: 90%
“…Most of the studies dedicated to analyze the destiny of the donor cells have been conducted using animal or human MSCs implanted into immunodeficient recipients such as nude mice, 1,20-23 NIH-Bg-nu-xid, 5,[24][25][26] and nude rats. 2,27,28 Several of these studies have shown that part of the donor cells can survive into the host for several weeks, leading to the conclusion that new bone originates from these surviving cells. 25,26 Other authors have suggested that the implanted cells could also, and perhaps principally, play a trophic role and increase local bone formation through the recruitment of hostderived stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used to tracking modified MSC in a bone defect did have obtained limited success, mainly because the label was not compatible with the specifics procedures used for bone histology 19 .In this study the bone samples used for evaluate CD+oMSC group were lost in procedures cause by bone histology preparation. However, the macroscopic findings after X-Gal staining gave us positive results, confirming the success of transplant.…”
Section: Discussionmentioning
confidence: 93%
“…Among the different techniques that have been proposed to track the fate of implanted cells in vivo, methods involving transduction of detectable genetic markers, such as those encoding for ß-galactosyltransferase (LacZ) and green fluorescent protein gene (GFP), are the only ones that allow stable and reliable long-term tracking of transplanted cells 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, when specific needs arise, as, for example, when immunostaining fibrillar collagens in bone embedded in an MMA resin system, primary fixation in 70% ethanol provides greater immuno-sensitivity over formalin (Wittenburg et al, 2009). Additionally, Hannouche et al (2007) found that a mixture of 2% formaldehyde and 0.2% glutaraldehyde gave superior results when detecting the LacZ gene expression in cells and sections of mineralized tissue embedded in MMA using the X-gal detection method.…”
Section: Specimen Preparationmentioning
confidence: 99%